Power Spectral Analyses of Index Finger Skin Blood Perfusion in Carpal Tunnel Syndrome and Diabetic Polyneuropathy. (3rd April 2011) - Huang, Han-Wei; Jou, I-Ming; Wang, Chien-Kuo; Chen, Pei-Yin; Wang, Wen-Chi; Lin, Chou-Ching K.
Abstract : The main purpose of this study was to investigate the applicability of frequency domain analysis on laser Doppler flowmetry (LDF) data recorded from the index fingers of patients with carpal tunnel syndrome (CTS) and diabetic polyneuropathy (DPN). Patients with numbness of the palm were recruited and grouped according to the results of electrophysiological examinations into 2×2 groups by the existence or nonexistence of CTS and/or DPN. Skin blood perfusion was recorded by LDF in both the neutral position and the maximally flexed position (the Phalen test).S -transformation was utilized to decompose the recorded data into frequency bands, and the relative band power and power dispersion were calculated. Analysis of variance was used to test the effects of DPN, CTS, and the Phalen test results. The results showed that (1) DPN decreased the absolute power and the relative power in some frequency bands in both positions and CTS increased the power dispersion of some frequency bands only during the Phalen test and (2) there was no difference in the LDF results between patients with positive or negative Phalen test results.